Pengembangan Industri Teri dalam Pemberdayaan Ekonomi Masyarakat Desa Padelegan Kecamatan Pademawu Kabupaten Pamekasan - Marsum Marsum; Syaiful Anam; Mohammad Fahrur Rozi; Suhaimi Suhaimi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Anchovies are widely consumed by the lower middle class, it turns out to be one of the best sources of calcium. The greatest calcium requirement occurs during growth and calcium is still needed even though it has reached adulthood to prevent osteoporosis. According to Hendradi (2009) anchovies are a source of calcium that is resistant and not easily dissolved in water. Anchovies are very good as a source of calcium that is cheap and easy to obtain. The development of the anchovy industry in empowering the economy of the Padelegan village community means that increasing the independence and welfare of the Padelegan village community is one of them through economic empowerment in the village in the digitalization era. Thematic KKN Group 05 Madura University activities carried out the development of the anchovy industry in empowering the economy of the Padelegan village community for one month with 11 work programs. This article was written using a qualitative study method with a descriptive approach.